Pastoral Conflict, Emerging Trends and Environmental Stress in Nyangatom, Southern Ethiopia - Temesgen Thomas Halabo; Taddesse Berisso (Ethiopian Journal of the Social Sciences and Humanities, 2020)
This study examined the dynamics of conflict, emerging trends and relationship between inter-pastoral conflicts and environmental changes in Nyangatom, Southern Ethiopia. The study employed a qualitative approach and exploratory case study research design. The study revealed that inter-pastoral conflicts stem from multiple and compounding dynamics. The environmental change has escalated intense inter-pastoralists’ contestation and conflicts, including cross-border conflict, on the scarce and fast-depleting natural resources. Indeed, there is a causal link between inter-pastoral conflicts and environmental changes. In this regard, the environmental factor has uniquely affected the Nyangatom due to the drying of Kibish River and rapid invasion of Prosopis–Juliflorain their key grazing lands. In response to environmental stresses as part of the traditional copying mechanism, the Nyangatom cross border deep into South-Sudan to their ethnic kin of Toposa and into Kenya that usually causes frequent cross-border conflicts with Turkana pastoralists. Irrespective of discernible risk of conflicts, they used to migrate to Mursi and Surma territories that causedconflict. And yet, the Nyangatom has often engaged in frequent conflicts with Dasanach. The study suggests alternative livelihood options and an understanding of the complex conflict dynamics in view of the cause-effect relationships for future management of inter-pastoral and cross-border conflicts in the region.